2017
DOI: 10.1002/qj.3053
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Pacific Meridional Mode on June–August precipitation in the Amazon River Basin

Abstract: This study examines the impacts of the Pacific Meridional Mode (PMM) on Amazon precipitation during June–August using observations and several experiments with the National Oceanic and Atmospheric Administration/Geophysical Fluid Dynamics Laboratory (NOAA/GFDL) Forecast‐oriented Low Ocean Resolution version of CM2.5 (FLOR). We find that the positive (negative) PMM can lead to precipitation surplus (deficit) using both observations and climate simulations with FLOR. The impacts of PMM on Amazon precipitation du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 72 publications
(137 reference statements)
2
15
0
Order By: Relevance
“…The Atlantic warming intensified the moisture transport convergence over tropical South America, which forms deep convection and thus enhances the local rainfall. SST warming in the North Atlantic plays a crucial role in causing the observed decadal change in the western North Pacific tropical cyclone frequency (Zhang et al 2017). We must pay great attention to Atlantic SST warming.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atlantic warming intensified the moisture transport convergence over tropical South America, which forms deep convection and thus enhances the local rainfall. SST warming in the North Atlantic plays a crucial role in causing the observed decadal change in the western North Pacific tropical cyclone frequency (Zhang et al 2017). We must pay great attention to Atlantic SST warming.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In recent decades, however, the dry season has been prolonged in the southern Amazon (since 1979), which is partly driven by the SST variability of the tropical Pacific and Atlantic, and is closely related to the shift of the subtropical jet in austral winter (Fu et al 2013). Zhang et al found that precipitation surplus (deficit) in the Amazon River basin during JJA (June, July and August) can be caused by the positive (negative) Pacific Meridional Mode (Zhang et al 2017); but only the tropical Atlantic meridional SST gradient is strongly associated with southern precipitation in JJA (Good et al 2008). Moreover, with the reductions in reflective aerosol pollution in the Northern Hemisphere, the risk of dry season (July-October) severe droughts (such as the 2005 droughts) is rapidly increasing over the Amazon in the 21st century (Cox et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to use real-time monitoring data to explain the impacts of spring freshet and summer rainfall flooding on lake water quality, because of insufficient manual monitoring times and the impact of flood disturbance on automatic monitoring systems. Thus, model simulation techniques are now being increasingly applied to simulate the impacts of these events on both water quantity and quality in many lakes [3,21,34]. Amongst these simulation tools is the commonly used MIKE 21 software.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to use real-time monitoring data to explain the impacts of spring freshet and summer rainfall flooding on lake water quality, because of insufficient manual monitoring times and the impact of flood disturbance on automatic monitoring systems. Thus, model simulation techniques are now being increasingly applied to simulate the impacts of these events on both water quantity and quality in many lakes (Moore, 2007;Chen et al, 2015;Zhang et al, 2017). Among these simulation tools is the commonly used MIKE 21 software.…”
Section: Introductionmentioning
confidence: 99%